(untitled) - Houlden, J. L. (Great Britian, 2006)
An account of the key historical, theological and cultural issues surrounding the enigmatic figure of Jesus. Written primarily for the enquiring lay person, this book that is useful to the believer and non-believer alike. It also provides an introduction for those studying the origins and evolution of Christianity as a major world religion.
Keywords: Jesus Christ -- Person and offices